Reka Cipta Media Cetak Sebagai Media Promosi - Yohanes Dimas Panji; Wahyu Wahyudi (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2023)
Today, health is an investment to support economic development and has an important role in efforts to reduce poverty. Health development must be seen as an investment to improve the quality of human resources. In measuring the Human Development Index (IPM), health is one of the main components besides education and income in Law Number 23 of 1992 concerning health it is stipulated that health is a state of well-being of body, soul and social that allows everyone to live productively socially and economy.